Whole-genome sequencing of a new sequence type (ST5352) strain of community-acquired methicillin-resistant Staphylococcus aureus from a hospital in Pakistan. (December 2019) - Ullah, Nimat; Raza, Tanzeela; Dar, Hamza Arshad; Shehroz, Muhammad; Zaheer, Tahreem; Naz, Kanwal; Ali, Amjad
Abstract: Objectives: Methicillin-resistant Staphylococcus aureus (MRSA) is an important drug-resistant pathogen causing a number of diseases, resulting in increased mortality. Therefore, whole-genome sequencing of an MRSA strain isolated from a patient admitted to a hospital in Lahore, Pakistan, was performed to better characterise the strain and to understand the genetic components of antimicrobial resistance and virulence. Methods: MRSA isolate Lr12 was sequenced on an Illumina HiSeq 2500 platform. The genome was assembled with SPAdes and was annotated using PGAP v.4.3. The strain was characterised using spa Typer 1.0, SCC mec Finder v.1.2 and MLST 2.0 server. Plasmids, antimicrobial resistance determinants and virulence factors were identified using PlasmidFinder v.2.0, CARD and VFDB, respectively. Results: MRSA strain Lr12 has an estimated genome size of 2 769 144 bp with a GC content of 32.7% and harbours 1 plasmid, 2 prophages, 11 antimicrobial resistance determinants and several virulence factors. The allelic profile of seven housekeeping genes was unique and the sequence type (ST) was classified as unknown, hence a novel sequence type (ST5352) was assigned. Conclusion: MRSA strain Lr12 has a novel sequence type (ST5352) and could be used as a reference strain for comparative genomic analysis of other MRSA strains belong to ST5352.